2021
DOI: 10.1136/annrheumdis-2021-219876
|View full text |Cite
|
Sign up to set email alerts
|

Olokizumab, a monoclonal antibody against interleukin 6, in combination with methotrexate in patients with rheumatoid arthritis inadequately controlled by methotrexate: efficacy and safety results of a randomised controlled phase III study

Abstract: ObjectiveTo evaluate the efficacy and safety of olokizumab (OKZ) in patients with active rheumatoid arthritis despite treatment with methotrexate (MTX).MethodsIn this 24-week multicentre, placebo-controlled, double-blind study, patients were randomised 1:1:1 to receive subcutaneously administered OKZ 64 mg once every 2 weeks, OKZ 64 mg once every 4 weeks, or placebo plus MTX. The primary efficacy endpoint was the proportion of patients achieving an American College of Rheumatology 20% (ACR20) response at week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 28 publications
0
23
0
13
Order By: Relevance
“…Promising pre-clinical evidence led to numerous clinical trials of the anti-IL6 antibody siltuximab to treat multiple myeloma or solid tumours, but these largely reported a lack of efficacy [79,295]. Although other novel anti-IL6 antibodies are being assessed for the treatment of immune disorders [297,298] or COVID19 (NCT04348500), further work is needed to evaluate their potential against BC.…”
Section: Therapeutic Targeting Of Gp130/il6st Signallingmentioning
confidence: 99%
“…Promising pre-clinical evidence led to numerous clinical trials of the anti-IL6 antibody siltuximab to treat multiple myeloma or solid tumours, but these largely reported a lack of efficacy [79,295]. Although other novel anti-IL6 antibodies are being assessed for the treatment of immune disorders [297,298] or COVID19 (NCT04348500), further work is needed to evaluate their potential against BC.…”
Section: Therapeutic Targeting Of Gp130/il6st Signallingmentioning
confidence: 99%
“…Siltuximab is currently studied for the treatment of COVID-19 and idiopathic multicentric Castleman disease (46)(47)(48). olokizumab is used in clinical trials for the treatment of rheumatoid arthritis with a remarkable therapeutic effect (49,50). Clazakizumab is beneficial not only for antibody-mediated rejection (51), but for active psoriatic arthritis (52).…”
Section: Discussionmentioning
confidence: 99%
“…Olokizumab (OKZ) is an IL-6 monoclonal antibody that can directly bind to IL-6 at specific sites. The results showed that there were significant differences in all secondary efficacy endpoints between the OKZ group and the placebo group, and more patients in the OKZ group reported adverse events (AEs), of which infection was the most common [36]. In conclusion, OKZ has more significance in the treatment of RA and has a high therapeutic potential value.…”
Section: Monoclonal Antibody Therapy Targeting Cytokinesmentioning
confidence: 92%